Impact of extraction processes on prebiotic potential of the brown seaweed Ecklonia radiata by in vitro human gut bacteria fermentation. (June 2016) - Charoensiddhi, Suvimol; Conlon, Michael A.; Vuaran, Michelle S.; Franco, Christopher M.M.; Zhang, Wei
Highlights: Extraction processes impact isolation of seaweed components with prebiotic potential. Enzyme extracted components stimulate beneficial microbes and SCFA output in vitro . The brown seaweed Ecklonia radiata has potential as a source of prebiotics. Abstract: The prebiotic potential of the extracts of a South Australian brown seaweed Ecklonia radiata obtained using different processes was investigated. Six extracts of this seaweed were prepared by enzymatic, acidic, and water extraction processes. The extracts were added to an in vitro anaerobic fermentation system containing human faecal inocula to assess their ability to generate short chain fatty acids (SCFAs) and to promote the growth of selected bacterial genera (as assessed by quantitative PCR). Following 24 h fermentation, all seaweed extracts significantly increased (P < 0.05) total SCFA production (50.7–72.7 µmol/mL) and the total number of bacteria (log10 10.2–10.4 cells/mL) when compared to controls (blank and cellulose). The extracts prepared using Celluclast-assisted extraction showed the greatest potential for improving gut health as these induced significantly higher production of butyrate (9.2 µmol/mL), and the growth of bacteria regarded as beneficial, including Bifidobacterium (log10 6.6 cells/mL) and Lactobacillus (log10 5.3 cells/mL).